أسباب الابتزاز الإلكتروني والآثار الاجتماعية والنفسية المرتبطة به: دراسة كيفية - السويدي، شريفة محمد; نوفل، زيزيت مصطفى عبده (جامعة بغداد - كلية الآداب, 2023)
هدفت الدراسة الحالية إلى الكشف عن أسباب تعرض الضحايا للابتزاز الإلكتروني، وأهم الآثار الاجتماعية والنفسية التي قد يعانون منها، ولتحقيق أهداف الدراسة تم استخدام المنهج الكيفي، إذ تكونت عينة الدراسة من (11) مبحوث، يعملون في القيادة العامة لشرطة الشارقة، ومركز الدعم الاجتماعي في إمارة الشارقة (ويتعاملون مع ضحايا الابتزاز الإلكتروني بشكل مباشر)، وتم اختيارهم قصديا، واستعملت المقابلة المعمقة كأداة للدراسة. وقد أظهرت نتائج الدراسة أن من أهم أسباب تعرض الفرد للابتزاز الإلكتروني هو الثقة المفرطة في الأشخاص الغرباء، وعدم الوعي، وضعف الوازع الديني، وغياب الرقابة الأسرية، والتفكك الأسري، ورغبة الضحية في ترك وقطع العلاقة مع الطرف الآخر (المبتز)، كما توصلت الدراسة إلى أن أكثر أشكال الابتزاز الإلكتروني انتشارا في إمارة الشارقة هو الابتزاز المادي والجنسي، وأن أبرز الآثار الاجتماعية التي قد يعاني منها الضحية هي: الميل إلى الانعزال، والخوف من العار والفضيحة والوصمة الاجتماعية، وقد يسهم في التفكك الأسري والعنف الأسري. أما بالنسبة للآثار النفسية فهي: فقدان الثقة في النفس وبالمحيطين، الشعور بالقلق والخوف والتوتر والاكتئاب ولوم الذات، والشعور بالخجل والندم، وقد يعاني من اضطراب نفسي يتطلب تدخل وعلاج طبي متخصص، وينخفض مستوى أداءه في الدراسة أو العمل، وقد يفكر في الإقدام على الانتحار. The current study aimed to reveal the causes of electronic extortion and the most important social and psychological effects that the victim may suffer from. To achieve the objectives of the study, a qualitative approach was used. The study sample consisted of (11) respondents who are working in the Sharjah”s Police and the Social Support Center in the Emirate of Sharjah (they are dealing directly with the victims of electronic extortion). The subjects were intentionally selected, and the in-depth interview was used as a study tool. The results of the study showed that the most important reasons for electronic extortion is excessive trust in strangers, lack of awareness, weak religious faith, absence of family control, family disintegration, and the victim's desire to leave and sever the relationship with the blackmailer. The study also concluded that the most common form of electronic extortion in the Emirate of Sharjah is financial and sexual extortion. And the most social effects that the victim may suffer from are: a tendency to isolate, fear of shame and social stigma, and it may contribute to family disintegration and the victim may be exposed to domestic violence. As for the psychological effects, they are: loss of self-confidence in oneself and those around him/her, feelings of anxiety, fear, stress, depression, self-blame, feelings of shame and remorse. S/He may suffer from a psychological disorder that requires specialized medical intervention and treatment, and her/his level of performance in study or work decreases and s/he may think of committing suicide.
Keywords: الجرائم الإلكترونية -- ضحايا الابتزاز -- الحماية القانونية -- شرطة الإنترنت -- مكافحة الجرائم